2019
DOI: 10.3766/jaaa.17123
|View full text |Cite
|
Sign up to set email alerts
|

Hormones and Hearing: Central Auditory Processing in Women

Abstract: Estrogen has been identified as playing a key role in many organ systems. Recently, estrogen has been found to be produced in the human brain and is believed contribute to central auditory processing. After menopause, a low estrogen state, many women report hearing loss but demonstrate no deficits in peripheral hearing sensitivity, which support the notion that estrogen plays an effect on central auditory processing. Although animal research on estrogen and hearing loss is extensive, there is little in the lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Although some studies have shown that ovarian hormones, including estrogen, may have a negative effect on the cochlear nerve, 35 most studies have reported that estrogen exerts a protective effect on hearing. 36 , 37 Previous studies have also demonstrated the expression of estrogen in the inner ear. 10 Moreover, estrogen can be produced by auditory neurons per se and directly affects neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies have shown that ovarian hormones, including estrogen, may have a negative effect on the cochlear nerve, 35 most studies have reported that estrogen exerts a protective effect on hearing. 36 , 37 Previous studies have also demonstrated the expression of estrogen in the inner ear. 10 Moreover, estrogen can be produced by auditory neurons per se and directly affects neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…High blood pressure may harm hearing due to pressure-induced microvascular atherosclerosis, which affects the auditory blood flow and causes hearing loss. 36 Long-term follow-up studies are required to validate this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Curhan et al (2017) observed that females who enter menopause at age 50 and older have a higher risk of self-reported hearing loss. Interestingly, a recent study showed that the decrease in estrogen following menopause is associated with difficulties in spatial hearing abilities as measured by the Listening in Spatialized Noise Test-Sentences (Trott et al 2019), supporting the importance of estrogen in central auditory processing. This is consistent with our results showing that inhibitory control is more significantly associated with SiN and spatial hearing abilities in aging females than in aging males.…”
Section: Ssq Scales Sinmentioning
confidence: 94%
“…In particular, a growing body of research shows that hormonal differences such as estrogen may contribute to sex differences in hearing [for a review, see, for example, Shuster et al (2019)] and is important for the prevention of age-related hearing loss (e.g., Simonoska et al 2009). The decrease in the level of estrogen following menopause has been associated with the onset of hearing loss (Kim et al 2002) and with deficits in spatial hearing abilities (Trott et al 2019). These findings highlight the importance of investigating the role of biological sex on the association between hearing loss and cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Five studies investigated auditory changes in post-menopausal women, with the sample size ranging from 22 to 190 participants (Tandon et al, 2001;Hederstierna et al, 2010;Svedbrant et al, 2015;Trott et al, 2019;Arora et al, 2021). One study tested participants three times (i.e., at 2, 7, and 10 years after the start of menopause) (Svedbrant et al, 2015).…”
Section: Auditory Changes In Post-menopausal Womenmentioning
confidence: 99%